2015
DOI: 10.1016/j.bbi.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex activation in conscious rats modulates the joint inflammatory response via sympathetic function

Abstract: The baroreflex is a critical physiological mechanism controlling cardiovascular function by modulating both the sympathetic and parasympathetic activities. Here, we report that electrical activation of the baroreflex attenuates joint inflammation in experimental arthritis induced by the administration of zymosan into the femorotibial cavity. Baroreflex activation combined with lumbar sympathectomy, adrenalectomy, celiac subdiaphragmatic vagotomy or splenectomy dissected the mechanisms involved in the inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 50 publications
4
47
0
2
Order By: Relevance
“…We recently reported that baroreflex activation through electrical stimulation of the aortic depressor nerve (ADN) attenuates, via sympathetic innervation, joint inflammation in a rat model of arthritis. Our results depicted the baroreflex antiinflammatory pathway as a new physiological mechanism of neuromodulation of inflammation and the innate immune system (Bassi et al, 2015). …”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…We recently reported that baroreflex activation through electrical stimulation of the aortic depressor nerve (ADN) attenuates, via sympathetic innervation, joint inflammation in a rat model of arthritis. Our results depicted the baroreflex antiinflammatory pathway as a new physiological mechanism of neuromodulation of inflammation and the innate immune system (Bassi et al, 2015). …”
Section: Introductionmentioning
confidence: 74%
“…We recently reported that baroreflex activation attenuates local inflammation in arthritic knee joints (Bassi et al, 2015). This mechanism significantly inhibits neutrophil recruitment, articular edema and inflammatory cytokine levels in the synovial fluid (Bassi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 In conscious rats, loss of baroreflex function impedes attenuation of peripheral ( joint) inflammation, mediated by sympathetic neural drive. 39 Thus, acute inflammation superimposed on a lack of established baroreflex 'reserve' may further detrimentally impair the neural anti-inflammatory armamentarium, which consequently jeopardizes metabolic homeostasis. 40 We found that established baroreflex dysfunction was associated with a higher incidence of intraoperative blood transfusion.…”
Section: Discussionmentioning
confidence: 99%